2008
DOI: 10.1300/j517v08n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Dublin Core Metadata Harvested Through OAI-PMH

Abstract: ABSTRACT. The introduction in 2001 of the Open Archives InitiativeProtocol for Metadata Harvesting (OAI-PMH) increased interest in and awareness of metadata quality issues relevant to digital library interoperability and the use of harvested metadata to build "union catalogs" Amy S. Jackson (E-mail: amyjacks@uiuc.edu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 11 publications
1
30
0
2
Order By: Relevance
“…CONTENTdm implementations are especially well suited for this sort of examination because the application gives implementers license to add locally defined metadata fields and the freedom to then map or not map these local fields to Dublin Core however the implementer sees fit for purposes of metadata record export. This paper stems in part from a finding described in the article Dublin Core Metadata Harvested through OAI-PMH (Jackson, Han, Groetsch, Mustafoff, & Cole, 2008). As described in this earlier paper, we found that "native metadata records are rich in meaning in their own environment, but lose richness in the aggregated environment due to the mapping errors and misunderstanding and misuse of Dublin Core elements" (Jackson et al, 2008, p. 18).…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…CONTENTdm implementations are especially well suited for this sort of examination because the application gives implementers license to add locally defined metadata fields and the freedom to then map or not map these local fields to Dublin Core however the implementer sees fit for purposes of metadata record export. This paper stems in part from a finding described in the article Dublin Core Metadata Harvested through OAI-PMH (Jackson, Han, Groetsch, Mustafoff, & Cole, 2008). As described in this earlier paper, we found that "native metadata records are rich in meaning in their own environment, but lose richness in the aggregated environment due to the mapping errors and misunderstanding and misuse of Dublin Core elements" (Jackson et al, 2008, p. 18).…”
Section: Introductionmentioning
confidence: 57%
“…Additionally, in part because of the widespread adoption of OAI-PMH within the library community (Brogan, 2006), which mandates Simple Dublin Core as the minimum requirement when exposing metadata to aggregators, the quality of harvested Dublin Core metadata has garnered much attention in several venues (Lagoze, 2004;Tennant, 2004;Ward, 2004;Hutt & Riley, 2005;Shreeves, Knutson, Stvilia, Palmer, Twidale, & Cole, 2005;Jackson et al, 2008). The issue of improving metadata, while using Simple Dublin Core as a minimum requirement in the OAI-PMH environment, has created a host of problems because Simple Dublin Core is viewed as semantically limited and has a flat structure.…”
Section: Shareable Metadatamentioning
confidence: 99%
See 2 more Smart Citations
“…Object types and formats are sometimes conflated, even within the same sentence, in the Description field, as well as in Objects Represented. This lack of disambiguation between type and format is a known metadata quality problem in digital object description (see, for example, Jackson et al, 2008).…”
Section: Resultsmentioning
confidence: 99%